Greenhouse gas emissions (GHGE), water footprint and nitrogen loss associated with food consumption among adults: findings from the updated LEBANese natiONal food consumption survey (LEBANON-FCS) - Maha Hoteit; Maroun Khattar; Esraa Antar; Dana Malli; The Adults-Lebanon-FCS Group (BMC Nutrition)
Abstract Background Lebanon is grappling with numerous environmental challenges, including water scarcity, landfill waste, deforestation, and rising air pollution. Food choices significantly influence global greenhouse gas emissions and environmental impacts, making it crucial to evaluate the environmental footprints (EFPs) of Lebanon’s current dietary habits. This study aimed to assess food consumption patterns and their EFPs among a nationally representative sample of Lebanese adults. Methods A cross-sectional survey was conducted from May to September 2022, involving 444 Lebanese adults aged 18 to 64 years. The sample was representative, and participants were distributed across the eight Lebanese governorates. Sociodemographic and medical data were collected via a questionnaire, food consumption was assessed through a validated Food Frequency Questionnaire (FFQ) and two non-consecutive 24-hour recalls, and anthropometric measurements were also taken. EFPs were derived from databases and repositories. Results The typical EFPs of an average Lebanese adult included water usage of 2,862.39 ± 1,617.88 L/day, greenhouse gas emissions of 4.43 ± 2.29 kg CO2-eq/day, and nitrogen use of 12.72 ± 6.76 g/day. Animal products were the primary contributors to greenhouse gas emissions, while vegetable products had the highest water footprint and nitrogen loss impact on the environment. Grains and cereals, the most consumed food category, significantly influenced the water footprint and nitrogen loss. Additionally, meat consumption notably drove greenhouse gas emissions. Conclusion Lebanon must address its environmental challenges and the impact of dietary choices on greenhouse gas emissions and EFPs. By evaluating and understanding the environmental consequences of current dietary patterns, Lebanon can take proactive steps towards promoting sustainable food practices and mitigating environmental degradation.